2013
DOI: 10.1073/pnas.1306859110
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 receptor antagonist prevents murine bronchopulmonary dysplasia induced by perinatal inflammation and hyperoxia

Abstract: Bronchopulmonary dysplasia (BPD) is a common lung disease of premature infants, with devastating short-and long-term consequences. The pathogenesis of BPD is multifactorial, but all triggers cause pulmonary inflammation. No therapy exists; therefore, we investigated whether the anti-inflammatory interleukin-1 receptor antagonist (IL-1Ra) prevents murine BPD. We precipitated BPD by perinatal inflammation (lipopolysaccharide injection to pregnant dams) and rearing pups in hyperoxia (65% or 85% O 2 ). Pups were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
142
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(155 citation statements)
references
References 42 publications
12
142
1
Order By: Relevance
“…Increased ROS production has been described in integrin α1-null glomerular mesangial cells (Chen et al, 2007); however, this has not previously been shown to occur in epithelial cells, and β1 integrins have not been linked to MCP-1 expression or ROS production in other systems. Although the role of macrophages during alveolarization is not well understood, we and others have shown that macrophages and macrophage-derived products disrupt branching morphogenesis (Blackwell et al, 2011;Nold et al, 2013). Specifically, we have found that products of activated macrophages can impair expression of molecules by epithelial and mesenchymal cells that are important for control of airway branching, including BMP4, Wnt7b and FGF10 (Benjamin et al, 2010;Blackwell et al, 2011;Carver et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
“…Increased ROS production has been described in integrin α1-null glomerular mesangial cells (Chen et al, 2007); however, this has not previously been shown to occur in epithelial cells, and β1 integrins have not been linked to MCP-1 expression or ROS production in other systems. Although the role of macrophages during alveolarization is not well understood, we and others have shown that macrophages and macrophage-derived products disrupt branching morphogenesis (Blackwell et al, 2011;Nold et al, 2013). Specifically, we have found that products of activated macrophages can impair expression of molecules by epithelial and mesenchymal cells that are important for control of airway branching, including BMP4, Wnt7b and FGF10 (Benjamin et al, 2010;Blackwell et al, 2011;Carver et al, 2013).…”
Section: Discussionmentioning
confidence: 73%
“…As expected, tracheal aspirates of infants exposed to hyperoxia had elevated inflammatory mediators primarily secreted by macrophages, notably IL-1b and tumor necrosis factor-a (14,15). In infants with sepsis-induced inflammation, inhibitors against the two cytokines showed little improvement in survival rates; in mouse models treated with inhibitors against these cytokines, only some BPD features improved (16)(17)(18)(19)(20). This suggests that alternative, more broadly functioning or upstream targets are needed to prevent BPD.…”
mentioning
confidence: 59%
“…After a call for more directed studies on pulmonary inflammation in BPD, clinical studies determined that inflammatory markers are not only elevated in BPD but associated with prognosis (12,15,39). Some studies used untargeted antiinflammatory therapies such as glucocorticoids, direct cytokines, or chemokines, which resulted in minimal improvement in some characteristics of BPD (19).…”
Section: Discussionmentioning
confidence: 99%
“…RT-PCR analysis showed increased inflammation in hyperoxic mice, including higher levels of interleukin (IL)-1␣ and macrophage inflammatory protein-1␣ (MIP-1␣), compared with controls. Administration of an IL-1␣ receptor antagonist in another model of BPD induced with prenatal lipopolysaccharide (LPS) and PN hyperoxia showed decreases in many inflammatory mediators, including but not limited to IL-1 (61). These data suggest that prolonged exposure to hyperoxia produces a physiological and histological picture similar to BPD, which may be mediated in part by inflammatory cytokines.…”
Section: Rodent Models Of Pulmonary Diseasementioning
confidence: 76%